Integrated nutrient management in fenugreek (Trigonella foenum-graecum L.) - A U Amin, B S Patel, S G Patel, S P Patel (Journal of Spices and Aromatic Crops, 2017)
A field experiment was conducted at Jagudan (Gujarat) to study the effect of integrated nutrientmanagement (INM) practices in fenugreek (Trigonella foenum-graecum). Growth and yieldattributes as well as seed and straw yields of fenugreek were significantly influenced by INMtreatments. Application of recommended dose through inorganic form with phosphatesolublizing bacteria @ 5 kg ha-1 gave higher growth and yield attributes and was at par withrecommended dose of fertilizer + Azotobacter sp. @ 5 kg ha-1 + 5 t farm yard manure ha-1 andrecommended dose of nitrogen + phosphate solublizing bacteria @ 5 kg ha-1 which weresignificantly superior to other treatments except test weight. This treatment also recordedsignificantly the highest grain and straw yields. The maximum net realization and benefit:costratio were obtained when the crop was fertilized with full dose of nitrogen and phosphoruswith phosphate solublizing bacteria @ 5 kg ha-1.